2022
DOI: 10.3389/fphar.2022.909363
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation, Pharmacokinetics, and Pharmacological Activities of Ginsenoside Rd Against Multiple Diseases

Abstract: Panax ginseng C.A. Mey. has a history of more than 4000 years and is widely used in Asian countries. Modern pharmacological studies have proved that ginsenosides and their compounds have a variety of significant biological activities on specific diseases, including neurodegenerative diseases, certain types of cancer, gastrointestinal disease, and metabolic diseases, in which most of the interest has focused on ginsenoside Rd. The evidentiary basis showed that ginsenoside Rd ameliorates ischemic stroke, nerve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…48,49 Ginsenoside Rg3 is a star component of panaxadiol saponins, which can effectively improve lipid metabolism disorders and reduce acute and chronic liver injury. 50,51 In addition, ginsenoside monomers such as Rb2, 52 compound K, 53 Rd, 54 and Rc 55 were also considered to be beneficial for liver protection. In view of the effectiveness of panaxadiol saponin monomers in metabolic liver disease, combined with network pharmacology analysis, we hypothesized that PDS-C may have beneficial effects in reducing blood sugar, serum lipid levels, and exhibiting anti-inflammatory and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Ginsenoside Rg3 is a star component of panaxadiol saponins, which can effectively improve lipid metabolism disorders and reduce acute and chronic liver injury. 50,51 In addition, ginsenoside monomers such as Rb2, 52 compound K, 53 Rd, 54 and Rc 55 were also considered to be beneficial for liver protection. In view of the effectiveness of panaxadiol saponin monomers in metabolic liver disease, combined with network pharmacology analysis, we hypothesized that PDS-C may have beneficial effects in reducing blood sugar, serum lipid levels, and exhibiting anti-inflammatory and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rd is mainly found in P. ginseng , and, to a lesser extent, in P. quinquefoliu and P. notoginseng [ 51 , 52 ]. Its chemical structure belongs to the protopanaxadiol group, in which various ginsenosides, such as Rb1, Rb2, and Rc, are capable of being transformed into Rd following absorption and metabolism in vivo [ 53 ]. Although the pharmacological function of Rd has been studied primarily as a neuroprotective agent based on its role in the potentiation of mitochondrial function and anti-inflammatory properties, recent evidence has demonstrated that Rd administration markedly improved hyperglycemia in diabetic rats fed a high-fat and high-sugar diet and administered streptozotocin by activating the Akt signaling pathway in the liver, resulting in increased glycogen synthesis and decreased hepatic gluconeogenesis [ 54 ].…”
Section: Pharmacological Effects Of Ginsenosides On Insulin Resistanc...mentioning
confidence: 99%
“…Although ginsenoside Rd is present in low concentrations in Panax species, it has attracted wide attention from scholars due to its strong biological activity. Studies have shown that ginsenoside Rd exhibits various pharmacological effects, such as protecting cardiovascular and renal functions, exerting anti-tumor and immunomodulatory activities, and showing good neuroprotective effects on the central nervous system ( Li et al, 2022b ; Tang et al, 2022 ). In terms of cerebral ischemia, ginsenoside Rd can improve ischemic stroke-induced damage by inhibiting oxidative stress and inflammation.…”
Section: Modulation Of Inflammasome In Is By Natural Plant Productsmentioning
confidence: 99%